A cross-sectional study of infant feeding practices in Vietnamese-born mothers living in Australia - Lauren Zahra; Peter Kremer; Kristy A. Bolton (BMC, 2022)
Abstract Background Infant feeding practices are a key modifiable risk factor for childhood overweight and obesity; and important for lifelong health and wellbeing. Despite the growing Australian immigrant population, it is unclear how infant feeding practices may differ between ethnicities living in Australia. Few studies have examined the infant feeding practices of Vietnamese mothers who migrate and give birth to infants in Australia - termed Vietnamese-born mothers. The aim of this study was to examine differences in infant feeding practices (breastfeeding, formula feeding and complementary feeding (other fluids and solids)) in Vietnamese-born mothers compared with Australian-born mothers living in Australia. Method This study analysed the Australian National Infant Feeding Survey dataset (2010-11), a large national cross-sectional survey measuring feeding practices of infants aged 0-24 months old. Infant feeding practices of Vietnamese-born mothers (n = 261) and a random sub-sample of Australian-born mothers (n = 261) were compared. Associations between ethnicity and infant feeding practices were examined through logistic and linear regression adjusting for maternal age, socioeconomic status, body mass index (BMI) at start of pregnancy, infant age at survey completion and parity. Compliance with the Australian national infant feeding guidelines was also assessed. Results Compliance with infant feeding guidelines was low, with differences in infant feeding practices between groups. At the time of survey completion, when infants were on average 7.2 months old, compared with infants of Australian-born mothers, infants to Vietnamese-born mothers were significantly younger when first exposed to fruit juice (b = -2.41, 95%CI: -4.54- -0.28); less likely to be exposed to solids (AOR: 0.15, 95%CI: 0.05-0.44) and more likely to be exposed to formula milks (AOR: 2.21, 95%CI: 1.10-4.43); toddler milks (AOR: 16.72, 95%CI: 3.11-90.09) and fruit juice (AOR: 2.37, 95%CI: 1.06-5.32) (p < 0.05). Conclusion Low adherence with breastfeeding (low breastfeeding and high infant formula use) and other fluids (toddler milks and fruit juice) recommendations outlined by the Australian infant feeding guidelines were observed in this group of Vietnamese-born mothers. To optimise feeding and growth in Vietnamese-Australian children, culturally appropriate infant feeding support targeting breastfeeding durations, reducing reliance on infant formula, and reducing inappropriate introduction to other fluids should be the focus of infant feeding promotion within these mothers.